Managing Meaning in Ukraine - Bolin, Göran (Information Policy, 2023)
An in-depth look at Ukraine's attempts to shape how it is perceived by the rest of the world.During times of crisis, competing narratives are often advanced to define what is happening, and the stakes of information management by nations are high. In this timely book, Göran Bolin and Per Ståhlberg examine the fraught intersection of state politics, corporate business, and civil activism to understand the dynamics and importance of meaning management in Ukraine. Drawing on fieldwork inside the country, the authors discuss the forms, agents, and platforms within the complex political and communicative situation and how each articulated and acted upon perceptions of the propaganda threat.Bolin and Ståhlberg focus their analysis on the period between 2013 and 2022, when political tensions, commercial dynamics, and new communication technologies bred novel forms of information management. As they show, entities from governments and governmental administration to commercial actors, entrepreneurs, and activists formed new alliances in order to claim a stake in information policy. Bolin and Ståhlberg also explore how the various agents engaged in information management and strove to manage meaning in communication practice; the communicative tools they took advantage of; and the subsequent consequences for narrative constructions.